Another reason for the counterintuitive effects of thank-you gifts on charitable giving - Fang, Zhou; Bian, Yong (Frontiers in Psychology, 2022)
Current studies on the effect of thank-you gifts on charitable giving are primarily based on the conclusion of a milestone paper, “The counterintuitive effects of thank-you gifts on charitable giving,” that the deduction is mainly driven by less feeling of altruism. The authors argue that a question design in “The counterintuitive effects of thank-you gifts on charitable giving” may lead to a biased conclusion. The authors added an extra treatment group to the original study and found that the authors neglected a critical impact of participants’ inference about the usage of the money. Keywords: thank-you gift, waste, donation, charitable giving, altruism